Baby Incubator Monitoring Center for Temperature and Humidity using WiFi Network - Luthfiyah, Sari; Kristya, Furi; Hari Wisana, I Dewa Gede; Thaseen, Mohseena (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2021)
Monitoring the condition of premature babies inside the baby incubator is very necessary. Babies who are born prematurely with a birth age of less than 38 weeks have a higher risk of death and difficulty to adapt outside the womb due to immaturity of the organ system. Premature babies need continuous monitoring by the nurse to find out the baby’s body condition remains stable in temperature and humidity to match the conditions in the womb. The purpose of this research to develop a baby incubator temperature and humidity monitoring system quickly and practically. As technology develops, the monitoring process that was initially carried out by looking directly at the baby incubator display, now developed with various innovations that make it easier to monitor premature babies. The baby incubator temperature and humidity monitoring center module via the WiFi network uses a temperature sensor and DHT 22 which will be sent via WiFi ESP 32 and the values ​​obtained will be displayed on the nextion tft display. Based on the measurement results obtained the largest temperature error value of 2.083% at the incubator client 1 temperature at the measurement point 32 ° C. The results showed that the device has an average error suitable for use, because based on ecri 415-20010301-01, the maximum allowable error limit is ± 1 ° C. The results of this study can be implemented to make it easier for nurses to monitor premature babies to avoid neglect.